ALIGNING ENGLISH FOR OCCUPATIONAL PURPOSES (EOP) WITH EMPLOYMENT DEMANDS: AN ANALYSIS - Abdul Ghani, Noor Amili; Md Idrus, Norazah; Ab Rahman, Hazlinah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
The increasing importance of English for Occupational Purposes (EOP) in meeting global employment demands has generated growing scholarly attention, yet research on its alignment with workplace needs remains fragmented. Addressing this gap, the present study conducts a bibliometric analysis to examine trends, patterns, and thematic structures in EOP-related research, offering insights into how English language education is adapting to labor market expectations. Using the Scopus advanced search, data were collected with the keywords “EOP,” “ESP,” “English for employment,” and “English at workplace,” resulting in a final dataset of 880 documents. To ensure reliability and consistency, the data were cleaned and harmonized using OpenRefine. The Scopus Analyzer was employed to generate descriptive statistics and graphical representations, identifying publication trends, prolific authors, active journals, and contributing countries. Furthermore, VOSviewer software (version 1.6.20) was applied to visualize co-authorship networks, co-citation patterns, and keyword co-occurrence, producing cluster maps that reveal the intellectual structure and thematic diversity of the field. The results highlight steady growth in EOP research, with notable contributions from Social Sciences, Education, and interdisciplinary studies, while keyword clustering identified nine major thematic areas, including workplace communication, employability skills, and curriculum design. These findings underscore the evolving role of English not merely as a linguistic competence but as a strategic skill directly tied to professional success in diverse employment contexts. The study concludes that EOP research is expanding in response to global labor market demands, though future studies must further bridge the gap between academic inquiry and practical workplace requirements. This bibliometric mapping provides both a comprehensive overview of the field and a roadmap for scholars, practitioners, and policymakers to strengthen the alignment of EOP with contemporary employment needs.